Regulation of seed germination by diurnally alternating temperatures in disturbance-adapted banana crop wild relatives (Musa acuminata) - Kallo, Simon; Davies, Rachel; Panis, Bartholomeus; Janssens, Steven B.; Vandelook, Filip; Mertens, Arne; Swennen, Rony L.; Tahir, Maimun Binti; Dickie, John (Cambridge University Press, 2020)
Seed conservation of banana crop wild relatives (Musa L. spp.) is limited because of lack of knowledge about their germination ecology. Musa acuminata Colla, the most important banana crop wild relative, is distributed in tropical and subtropical Asian and Pacific rainforests and colonizes disturbed sites. The role of temperature in stimulating/inhibiting germination to detect disturbance when canopy gaps are formed is not well known. We assessed seed germination thermal requirements of three subspecies of M. acuminata using nine seed accessions which had been stored in the Millennium Seed Bank. Diurnally alternating temperature cycles were almost completely essential for germination compared with constant temperatures. Germination was optimal when the upper temperature of a diurnal cycle was at 35°C; the lower temperature of the cycle was less important. Subspecies occurrence coordinates were used to extract climate temperature data which were then compared against the temperature requirements for germination from our experiment results. Maximum temperatures of the warmest month across subspecies ranges were close to but below optimal germination temperatures, as were diurnal ranges, suggesting soil-warming at the micro-climate level following gap creation is important for M. acuminata seed germination. Additionally, pre-treatment for 3 months at 60% relative humidity at constant 25°C improved germination from 14 ± 10 (mean, standard deviation) to 41 ± 29% suggesting a period in the soil seed bank under the canopy may increase sensitivity to alternating temperature cycles. Overall viability was low (49 ± 28%), and considerable variance was caused by the different accessions. Germination remained somewhat inconsistent.